Safety effectiveness of adding by-pass lanes at unsignalized rural intersections in Kansas - Shams Esfandabadi, Alireza (Kansas State University, 2014)
Construction of by-pass lanes at rural intersections typically has been considered a low-cost safety improvement. Safety analysis utilizes two common approaches to evaluate treatment effectiveness: before-and-after study and cross-sectional study. This research performed paired sample t-test statistical analysis to estimate changes in total of crash frequency, crash rates, EPDO crash frequency, and EPDO crash rates at intersections, three to five years after adding a by-pass lane compared to identical time period before the by-pass lane was added. Crash data between 1990 and 2011 were obtained from Kansas Crash and Analysis Record System (KCARS) maintained by the Kansas Department of Transportation (KDOT). In order to perform a cross-sectional study, intersections with by-pass lanes were compared to intersections with no countermeasures; crash data were obtained for more than 1,100 intersections in the state of Kansas. According to before-and-after study, addition of by-pass lanes improves safety at unsignalized rural intersections; crashes and their severities are reduced after adding by-pass lanes. But, these reductions are not statistically significant under 95% confidence level. However, when considering intersection related crashes, a statistically significant reduction in crash rates is happened after adding by-pass lanes at 3-legged intersections. In cross-sectional study, crashes and their severities are lower at 3-legged intersections with the by-pass lanes versus 3-legged intersections without the by-pass lanes. However, these reductions are not statistically significant under 95% confidence level. When considering 300 feet intersection crash box, statistically significant reductions are happened at 4-legged intersection. In contrast, crashes and their severities increased at 4-legged intersections with the by-pass lanes, but these changes are not statistically significant under 95% confidence level. The Crash Modification Factors were calculated to evaluate safety effectiveness of adding by-pass lanes at unsignalized rural intersections. The calculated CMFs less than 1.0, indicate a reduction in crashes after implementation of by-pass lanes. Finally, this study concluded that expected crashes at intersections with by-pass lanes are lower than intersections without by-pass lanes.
Keywords: By-pass Lanes; Before-and-After Study; Cross-Sectional Study; Crash Modification Factor; Unsignalized Rural Intersections; Civil Engineering (0543)